2008
DOI: 10.1037/0735-7036.122.4.428
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of visual attention by adult humans (Homo sapiens): A partial replication of Povinelli, Bierschwale, and Čech (1999).

Abstract: Povinelli, Bierschwale, and Cech (1999) reported that when tested on a visual attention task, the behavior of juvenile chimpanzees did not support a high-level understanding of visual attention. This study replicates their research using adult humans and aims to investigate the validity of their experimental design. Participants were trained to respond to pointing cues given by an experimenter, and then tested on their ability to locate hidden objects from visual cues. Povinelli et al.'s assertion that the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The chimpanzees’ superior performance in this condition was interpreted by Povinelli et al (1999) as evidence for inferior cognitive representations of visual perspective. However, Thomas et al (2008) showed that human adults responded more like the chimpanzees under these experimental conditions. Again, apes’ performance was incorrectly interpreted as evidence for cognitive inferiority on the basis of a difference in behavior.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The chimpanzees’ superior performance in this condition was interpreted by Povinelli et al (1999) as evidence for inferior cognitive representations of visual perspective. However, Thomas et al (2008) showed that human adults responded more like the chimpanzees under these experimental conditions. Again, apes’ performance was incorrectly interpreted as evidence for cognitive inferiority on the basis of a difference in behavior.…”
Section: Discussionmentioning
confidence: 84%
“…This highlights the difficulty in elucidating cognitive mechanisms, particularly when experiments use flawed sampling procedures or have little control over subject variables, (e.g. Bulloch et al 2008; Furlong et al 2008; Hostetter et al 2007; Leavens et al 2008; Thomas et al 2008). There is little question that future cross-species studies are of tremendous importance in further delineating the evolution of human cognition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, with respect to matching apes and humans on age (or life history stage), Horowitz (2003) tested human adults on an imitation task and found that they, like adult chimpanzees, tended not to precisely mimic human demonstrators, but to use idiosyncratic means for opening an “artificial fruit” (see Whiten, Custance, Gómez, Teixidor, & Bard, 1996, for a description of this apparatus and procedure; also see Froese & Leavens, 2014, for a new theory of imitation based on these findings). Thomas, Murphy, Pitt, Rivers, and Leavens (2008) exposed human adults to an experimental condition in which the participants were required to find hidden rewards in one of two possible locations, based, in one condition, on an experimenter's gaze to a fixation point in the same hemispace, but directed above, not directly at, a baited container. In the original study by Povinelli et al (1999), adolescent chimpanzees performed above chance in this condition, whereas human 3-year-old children performed at chance (i.e., the chimpanzees were more successful than the children).…”
mentioning
confidence: 99%
“…This highlights the difficulty in elucidating cognitive mechanisms, particularly when experiments use flawed sampling procedures or have little control over subject variables, (e.g. Bulloch et al 2008;Hostetter et al 2007;Leavens et al 2008;Thomas et al 2008). There is little question that future cross-species studies are of tremendous importance in further delineating the evolution of human cognition.…”
Section: Discussionmentioning
confidence: 99%